THE RHYTHM OF THOUGHT: EXPLORING CHOMSKY'S VISIONARY LINGUISTIC THEORIES - Singh , Rajesh Kumar; Sharma, Anita Jyoti (International Research Journal of Arts and Communication, 2024)
In his exploration of language, Noam Chomsky introduces the notion of a "stimulus-free language," challenging conventional understandings of linguistic development and expression. This abstract delves into Chomsky's vision for a linguistic landscape emancipated from the constraints of external and internal stimuli. By envisioning language as a symphony of creativity and boundless expression, Chomsky offers a profound reimagining of human communication. Through this lens, we examine the transformative potential of Chomsky's ideas, their impact on linguistic theory, and their resonance in the broader fields of cognitive science and cultural studies. These abstract invites readers to embark on a journey through the realms of language, exploring Chomsky's visionary quest to liberate the human voice from linguistic chains.